Cationically functionalized dextrin polymer as an efficient flocculant for harvesting microalgae. (November 2020) - Kumar, Niwas; Banerjee, Chiranjib; Jagadevan, Sheeja
Abstract: The present study sets out to the development of cationic graft copolymer, dextrin -g-PMETAC through grafting of 2-methacryloyloxyethyl trimethyl ammonium chloride (METAC) on to the dextrin polymer. Flocculation efficiency of this graft cationic copolymer was studied towards the biomass harvesting efficiency of three indigenous microalgal strains viz, Scenedesmus  sp. CBIIT(ISM), Micractinium  sp. NCS2 and Chlorella  sp. NCQ. The results demonstrated that the synthesized copolymer was very effective in microalgal dewatering. The biomass harvesting efficiency of the dextrin-g-PMETAC for Scenedesmus  sp. CBIIT(ISM), Micractinium  sp. NCS2 and Chlorella  sp. NCQ was 98.87 ± 0.17 %, 98.19 ± 0.22 % and 97.56 ± 0.28 % at optimized dosage of flocculant 25 ppm 35 ppm and 45 ppm respectively. Comparative study of biomass composition of polymer induced flocculated biomass and centrifuged biomass in terms of proteins, carbohydrates, lipids, and residual ash content indicated that the biomass harvesting through dextrin-g-PMETAC does not affect the characteristics of microalgal biomass. Based on the obtained results, dextrin-g-PMETAC could be considered as an efficient polymeric flocculant towards the harvesting of microalgae. Graphical abstract: Highlights: Dextrin based cationic polymer dextrin-g-PMEATC was synthesized and characterized. The dextrin-g-PMETAC polymer was found to be better flocculant than dextrin. At optimized dosages more than 97% harvesting efficiency was achieved. Synthesized polymer do not interfere with the metabolite extraction from microalgae.